2001
DOI: 10.1207/s15328023top2802_05
|View full text |Cite
|
Sign up to set email alerts
|

Using Ignorance Questions to Promote Thinking Skills

Abstract: In this article I explore the educational value of students writing questions on what they do not know about course content. Students bring questions to class on assigned chapters and we discuss the questions. Later, students write 1 question for each exam. Students in 10 classes agreed that the technique helped them see alternative ways of viewing the course material, understand the limitations of texts and lectures, and relate current information to previously learned material. This technique is applicable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Results showed that when students completed the four questions prior to the quiz, their performance on the quiz was significantly better than when students completed the four questions after the quiz. Results suggest that when students spend time thinking and elaborating on the material in multiple ways, their performance on comprehension tests improves, consistent with prior research (e.g., Anderson, 1978;Carroll, 2001;DeRosa, 1988;Hyde & Jenkins, 1969;Kolers, 1979;Roediger et al, 2002). Moreover, students perceived that the four-questions technique successfully met its objectives and they enjoyed responding to the questions.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Results showed that when students completed the four questions prior to the quiz, their performance on the quiz was significantly better than when students completed the four questions after the quiz. Results suggest that when students spend time thinking and elaborating on the material in multiple ways, their performance on comprehension tests improves, consistent with prior research (e.g., Anderson, 1978;Carroll, 2001;DeRosa, 1988;Hyde & Jenkins, 1969;Kolers, 1979;Roediger et al, 2002). Moreover, students perceived that the four-questions technique successfully met its objectives and they enjoyed responding to the questions.…”
Section: Discussionsupporting
confidence: 86%
“…A third way to promote deeper thinking is questioning, whereby students generate a question they still have about the material, thus encouraging deeper processing of the material. Carroll (2001) found that students reported favorable attitudes toward having to generate questions about course content. In a review of the cognitive psychology literature, Anderson (1978) found strong support for the role of question generation in improving memory.…”
Section: Using the Four-questions Technique To Enhance Learningmentioning
confidence: 99%
“…Other research suggests that the combination of brief writing with discussion may be more effective pedagogically than discussion alone. For instance, class discussion can be facilitated by having students prepare questions (Carroll, 2001) and talking points prior to class (Connor-Greene, 2005).Our study expanded on previous research in several ways. First, we used the minute-paper technique with topics typically reserved for discussions and for which there are no "right" answers.…”
mentioning
confidence: 84%
“…Elaboration of the material, which involves interpreting information, connecting it with other information, and mulling it over is an important aspect of deeper encoding of information. Other techniques that strengthen encoding and that promote deeper thinking are conscious retrieval of the information, practice that is distributed in time (Smith & Kosslyn, 2007), and generation of questions about the material (e.g., Carroll, 2001;Dietz-Uhler & Lanter, 2009). In addition, distinctiveness, and information that is selfreferenced facilitate memory for course content (e.g., Cherney, 2008;Hartlep & Forsyth, 2000;Roediger, Gallo, & Geraci, 2002;VanderStoep, Fagerlin, & Feenstra, 2000).…”
Section: Why Is Active Learning Important?mentioning
confidence: 99%